Comparing the effectiveness of cognitive-behavioral therapy and parent-child interaction therapy on Parent-child interaction in children with separation anxiety disorder - Kianoosh, Zeinab; Mirzaian, Bahram; Nejat, Hamid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Anxiety disorders have significant negative effects on children’s academic performance, relationships with peers, and family functioning. The purpose of the present study was to compare the effectiveness of cognitive-behavioral therapy and parent-child interaction therapy on Parent-child interaction in children with separation anxiety disorder. Methods: The current research was of the type of practical and quasi-experimental designs of pre-test-post-test and follow-up with a control group. The statistical population of this research included all children (girls and boys) suffering from separation anxiety disorder in Sari city in the first six months of 2021. The sample of this research includes 30 people who referred to Bamdad Counseling Center and Bavar Counseling Center who were selected using available sampling method and randomly divided into two experimental groups of cognitive-behavioral therapy and parent-child interaction therapy and the control group in the list. They waited. The data were obtained using the Strauss Parent-child interaction Questionnaire (1990), Spence Children’s Anxiety Scale (1997). The data was analyzed using the method of analysis of variance with repeated measurements and SPSS-26 software. Results: The results showed that there is a significant difference between the two groups of cognitive-behavioral therapy and parent-child interaction therapy on Parent-child interaction in children with separation anxiety disorder (F=14.09; P<0.001). And cognitive behavioral therapy had a greater effect than parent-child interaction therapy on Parent-child interaction in children with separation anxiety disorder (P<0.001). Conclusion: Therefore, it can be concluded that cognitive behavioral therapy can be an effective intervention method to improve Parent-child interaction in children with separation anxiety disorder.